MENINGKATKAN MINAT DAN KEMAMPUAN MEMBACA SISWA DI MADRASAH - Arafat, Yasir (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2017)
Reading is a skill. The scarcity of books read had an impact on a person's ability in speaking and writing for it, keep the earnest efforts of self to always increase-right quality and quantity of reading. Language experts concluded that the movement of the eyeball time reading changed his line with his goals, changes a person's ability to understand reading materials significantly influenced by the purpose to read it (a clear goal will improve reading comprehension, while a less obvious purpose will hinder comprehension, reading purpose-formulated clearly will affect the acquisition of reading comprehension). Someone who has the ability to read high (good), able to utilize the technique of reading which varies in line with the goal of reading that would be achieved. The conclusions made by experts in the above languages have shown clearly that there is an influence of the dominant reading purpose in the process of reading, especially against the results of understanding what is read. The clear objective would increase the interest and ability to read to someone. A person who is fully aware will aim to read it will be able to redirect the target of critical thought in power manipulate the reading material so as to obtain satisfaction in reading. Keywords: Interest, Ability and Reading